The Biology of Chronic Lymphocytic Leukemia: Diagnostic and Prognostic Implications. Issue 4 (July 2021) - Moia, Riccardo; Patriarca, Andrea; Schipani, Mattia; Gaidano, Gianluca
Abstract : Abstract: The high degree of clinical heterogeneity of chronic lymphocytic leukemia (CLL) is influenced by the disease molecular complexity. Genetic studies have allowed to better understand CLL biology and to identify molecular biomarkers of clinical relevance. TP53 disruption represents the strongest prognosticator of chemorefractoriness and indicates the use of Bruton tyrosine kinase inhibitors (BTKis) and BCL2 inhibitors. Unmutated IGHV (immunoglobulin heavy variable) genes also predict refractoriness to chemoimmunotherapy; importantly, when treated with B-cell receptor inhibitors or BCL2 inhibitors, IGHV unmutated patients display an outcome similar to that of IGHV mutated CLL. Before choosing treatment, a comprehensive assessment of TP53 and IGHV status is recommended by all guidelines for CLL clinical management. In case of fixed-duration therapeutic strategies, monitoring of minimal residual disease may provide a tool to decide treatment duration. The current precision medicine management of CLL patients might be further improved by the adoption of novel biomarkers that are emerging as clinically meaningful for this disease.